1998
DOI: 10.1016/s0014-5793(98)01229-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective suppression of stress‐activated protein kinase pathway by protein phosphatase 2C in mammalian cells

Abstract: Protein phosphatase 2CK K (PP2CK K) or PP2CL L-1 expressed in COS7 cells suppressed anisomycin-and NaClenhanced phosphorylations of p38 co-expressed in the cells. PP2CK K or PP2CL L-1 expression also suppressed both basal and stress-enhanced phosphorylations of MKK3b and MKK6b, which are upstream protein kinases of p38, and of MKK4, which is one of the major upstream protein kinases of JNK. Basal activity of MKK7, another upstream protein kinase of JNK, was also suppressed by PP2CK K or PP2CL L-1 expression. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 34 publications
3
92
0
1
Order By: Relevance
“…We have recently reported that ectopic expression of mouse PP2C␣ or PP2C␤-1 inhibited the stress-activated MKK3/6-p38 and MKK4/7-JNK pathways but not the mitogen-activated MKK1-ERK1 pathway. Thus, negative regulation by PP2C␣ and PP2C␤-1 is selective for different SAPK pathways (17). Essentially the same results were obtained in studies of human PP2C␣-1 and -2 in mammalian cells (14).…”
supporting
confidence: 68%
“…We have recently reported that ectopic expression of mouse PP2C␣ or PP2C␤-1 inhibited the stress-activated MKK3/6-p38 and MKK4/7-JNK pathways but not the mitogen-activated MKK1-ERK1 pathway. Thus, negative regulation by PP2C␣ and PP2C␤-1 is selective for different SAPK pathways (17). Essentially the same results were obtained in studies of human PP2C␣-1 and -2 in mammalian cells (14).…”
supporting
confidence: 68%
“…12,13 The extent and specificity of JNK activation serve as important signals for promoting the stabilization and transcriptional activity of JNK substrates, which then mediate cell survival and/or apoptosis. Although phosphatases capable of dephosphorylating JNK cascade substrates have been deemed the primary negative regulators of JNK signaling, 14,15 several other proteins inhibit mitogen-activated kinase kinases (MAPKKs) signaling by interacting physically with various cascade components. [16][17][18] Thus, the precise molecular mechanism(s) that modulate JNK activation have yet to be completely elucidated.…”
mentioning
confidence: 99%
“…Marley et al (38) reported that deletion of the C-terminal residues (including Arg 174 ) results in a completely inactive protein. In addition, replacement of Arg 179 (corresponding to Arg 174 of PP2C␣) with Gly in PP2C␤ results in a nearly complete loss of enzymatic activity (18). Therefore, Arg 174 may be necessary for the phosphatase activity of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of Mutant PP2C␣ and Preparation of Recombinant Adenovirus-The recombinant vector containing HA-tagged mouse PP2C␣ cDNA was generated as described previously (18). A QuikChange sitedirected mutagenesis kit (Stratagene, La Jolla, CA) was used for mutagenesis.…”
Section: Methodsmentioning
confidence: 99%